Pendekatan Saddu Al-Dzari,ah dalam Studi Islam - Siregar, Ramadani (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
The growth and development of the social dynamics of society continues to move so that it affects the legal system in it. Saddu al-Dzari’ah is a method of making legal decisions (istinbath al-hukum) in Islam. Saddu al-Dzari’ah is a method produced by previous ushul fiqih scholars in an effort to keep humans as mukallaf so as not to fall into damage (mufsadah). Saddu al-Dzari’ah has three main elements that need to be considered, namely the first goal or intention to be desired, if the goal is for evil then the path is prohibited and if the goal is good then the path is obligatory second, the intention or motive from the point of view of the target, if the intention is to achieve what is lawful, then the law of the means is lawful, if the intention is to be achieved is unlawful, then way to take that path is also unlawful. The third is the result of an action taken. By using the Saddu al-Dzari’ah method, it is hoped that Islamic law will always place legal issues proportionally and prioritize the benefits and benefits of law for the community. The author describes an explanation of Saddu al-Dzari’ah, so that it has the conclusion that Saddu al-Dzari’ah is a preventive method in order to guard against bad possibilities and so that things do not happen that have a negative impact.